Information behaviour research in Eastern Europe in 2013-2022 - Elena Maceviciute (Informatio)
The aim of this text is to introduce a general overview of the information behaviour research done by Eastern and Central Europe researchers (or the previously socialist space) over the last decade. Thus, research, which was done by outsiders about this region, is not included in the review.